Core–shell Co3O4/α-Fe2O3 heterostructure nanofibers with enhanced gas sensing properties1. Issue 46 (23rd May 2015) - Cao, Jing; Wang, Ziying; Wang, Rui; Liu, Sen; Fei, Teng; Wang, Lijie; Zhang, Tong
<x xml:space="preserve">Abstract</x> 1D Co3O4/α-Fe2O3 core–shell nanofibers were successfully fabricated by a facile and template-free coaxial electrospinning method, and developed for acetone gas detection.